Use of Computer for Calculating the "Internal Rate of Return" of Teak Plantations in Thana Forests of Maharashtra State - Joshi, N. J. (Indian Forester, 1975)
The paper explains tbe use of computer for calculating tbe Internal Rate of Return by means of Internal halving programme prepared by Dr. R. B. Ferster of the Economic Institute, Ottawa, Canada. The paper explains draw backs of the system adopted for calculating the rate of return without the use of computer and in the end gives the Internal Rates of Return of Teak plantations in Thana forests for various rotations as calculated with the help of a computer and without the help of a computer.